2022
DOI: 10.1158/0008-5472.can-22-1159
|View full text |Cite
|
Sign up to set email alerts
|

MEX3A Mediates p53 Degradation to Suppress Ferroptosis and Facilitate Ovarian Cancer Tumorigenesis

Abstract: Epithelial ovarian cancer (OC) is a highly heterogeneous and malignant female cancer with an overall low survival rate. Mutations in p53 are prevalent in the major OC histotype, high-grade serous ovarian carcinoma (HGSOC), while p53 mutations are much less frequent in other OC subtypes, particularly in ovarian clear cell carcinoma (OCCC). Advanced stage OCCC with wildtype (WT) p53 has a worse prognosis and increased drug resistance, metastasis, and recurrence than HGSOC. The mechanisms responsible for driving … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Previous studies revealed that p53 inhibited the expression of SLC7A11, which in turn inhibited cystine uptake and induced ferroptosis [ 32 ]. In OC, MEX3A mediated degradation of p53 to inhibit ferroptosis and promote OC tumor progression [ 33 ]. In another study on the application of PARP inhibitors in OC, researchers found that PARP inhibition promoted ferroptosis by inhibiting SLC7A11 in a p53-dependent manner [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that p53 inhibited the expression of SLC7A11, which in turn inhibited cystine uptake and induced ferroptosis [ 32 ]. In OC, MEX3A mediated degradation of p53 to inhibit ferroptosis and promote OC tumor progression [ 33 ]. In another study on the application of PARP inhibitors in OC, researchers found that PARP inhibition promoted ferroptosis by inhibiting SLC7A11 in a p53-dependent manner [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike traditional apoptosis, necrosis, and autophagy, ferroptosis is due to excess intracellular iron ions, leading to oxidative stress and cell death, and has been linked to the development of many cancers, including OC [ 175 , 176 ]. MEX3A is an evolutionarily conserved RNA binding protein (RBP) involved in cellular ferroptosis and is involved in various tumorigenesis by regulating mRNA stability, transport and translocation [ 177 179 ]. On the one hand, MEX3A can affect the distribution and utilization of intracellular iron ions by inhibiting the expression of iron metabolism-related genes FTH1 and FPN and regulating intracellular iron ion transport and storage, thus reducing the level of intracellular free iron ions and alleviating oxidative stress and cell death; On the other hand, MEX3A can also cause p53 protein degradation and enhance tumorigenesis [ 179 ].…”
Section: Novel Therapeutic Strategiesmentioning
confidence: 99%
“…[2] Characterized by high heterogeneous and high aggression, OC patients experience a poor clinical outcome having a 5-year survival rate less than 50%. [3,4] Despite immunotherapy as a promising modality for many cancer, [5] the evidences about OC response to immunotherapy are limited. Moreover, there are few clinical markers that can effectively predict the prognosis of OC patients.…”
Section: Introductionmentioning
confidence: 99%